Argentina's Economic Reforms of the 1990s in Contemporary and Historical Perspective - Cavallo, Domingo; Cavallo Runde, Sonia (Taylor & Francis, 2017)
Why has Argentina suffered so much political and economic instability? How could Argentina, once one of the wealthiest countries in the world, failed to meet its potential over decades? What lessons can we take from Argentina's successes and failures?$1!# (BArgentina$1 (Bs economy is - irresistibly - fascinating. Argentina's economic history - its crises and its triumphs cannot be explained in purely economic terms. Argentina's economic history can only be explained in the context of conflicts of interest, of politics, war and peace, boom and bust. Argentina's economic history is also intertwined with ideological$1!# (Bstruggles over the ideal society and the on-going struggle of ideas. $1!# (BThe book comprises two distinct components: an economic history of Argentina from the Spanish colonial period to 1990, followed by a narrative by Domingo Cavallo on the last 25 years of reform and counter reform. Domingo Cavallo has been at the centre of Argentina's economic and political debates for 40 years. He was one of the longest serving cabinet members since the return of democracy in 1983. He is uniquely qualified to help the reader make the connection between historical and current events through all these prisms. His daughter, Sonia Cavallo Runde, is an economist specialized on public policy that currently teaches the politics of development policy. The two Cavallos offer academics and students of economics and finance a long form case study. This book also seeks to offer researchers and policymakers around the world with relevant lessons and insights to similar problems from the Argentine experience.s
English
Keywords: Business & management; Development economics & emerging economies; Finance; Encyclopaedias & reference works; Business and Management; Development economics and emerging economies; Finance; Encyclopaedias and reference works